Agrotóxico X agroecologia : realidade e perspectivas para o Assentamento Dom Fernando - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This research presents a discussion about the conflict between agribusiness and social movements, having as its apex the materialization of this reality in the Dom Fernando settlement, located in the municipality of Itaberaí-GO. It is assumed that this conflict is a historical condition in Brazil. It begins with the arrival of colonizers and intensifies over the course of Brazilian territorial formation, given the capitalist management of the territory that prioritized the privatization of land. On the other hand, social movements in and in the countryside triggered and continue to trigger a struggle for social justice that involves access to land. It is understood that the Brazilian countryside, from the 1970s, became the locus of the territorial expansion of international capital, driven by the expanded accumulation of capital by large corporations. In this context, there is a reaction from social movements proposing alternative forms of production, which allow liberation from the agribusiness network. For the understanding of this condition, the Dom Fernando Settlement is essential, in view of the materiality of the conflict between agribusiness and agroecology. The presence of agribusiness in Dom Fernando is due to the enclosure of the orange monoculture that requires the intensive use of pesticides, which negatively impacts the health of the settlers and food production. On the other hand, there is the attempt to develop agroecological production, which, in turn, suffers resistance from the settlers and orange producers who depend on the labor of the families that live in the settlement. Therefore, it has no interest in their financial independence. As a methodological procedure, a bibliographical analysis was carried out, which provided the theoretical basis for understanding the factors that make up the development of capitalism in the Brazilian countryside and its interference in the formation of the Dom Fernando settlement. A bibliographical analysis was also carried out on the socio-environmental effects of the use of pesticides, with emphasis on the health of rural workers and, evidently, of workers and residents in the Dom Fernando settlement. The field research procedure helped in the articulation between theory and practice. Thus, empirical information was obtained through on-site work in the settlement in question. As a result of the research, it presents the clash between agribusiness, represented by the Orange monoculture that negatively impacts the existence of the settlers, and the development of agroecological activities that seek to guarantee the existence of the Dom Fernando Settlement and the autonomy of the settlers.
Agrotoxics X agroecology: reality and perspectives for the Dom Fernando Settlement
Keywords: Conflito; Agronegócio; Agroecologia; Assentamento Dom Fernando; Conflict; Agribusiness; Agroecology; Settlement Don Fernando.; GEOGRAFIA HUMANA::GEOGRAFIA AGRARIA